Immunization Coverage of Underfives in Marunda, North Jakarta - Titi Sunarwati Sularyo; Sri Rochani Sudjarwo (Indonesian Pediatric Society, 1995)
A study was prospectively carried out on the immunization coverage of underfives in a rural coastal area in Marunda, North Jakarta. It revealed that (1) the immunization coverage was still far below target, to wit covering only 19.6 % of the 102 studied children except for BCG which fulfilled the national target; (2) the immunization coverage was significantly associated with the Road to Health Chart (KMS) utilization (p < 0.05), the number of mother's parity (p < 0.05), and very significantly associated (p < 0.01) with the family income; (3) Mothers reasons for not having their underfives immunized were not knowing at all about immunization or that it should be done consecutively several times (65.9 %), the child was then not considered quite healthy (15.8 %), or there had been no funds (18.3 %).